Health Related Quality of Life Among Coronary Artery Bypass Graft Patient Attended at Combined Military Hospital, Dhaka (Anwer Khan Modern Medical College Journal, 2013)
This descriptive type of cross sectional study was carried out among purposively selected 90 coronary artery bypass graft operated patients attended at cardiovascular surgery out patient department of combined military hospital, Dhaka from 01 March 2012 to 30 June 2012 with the objective to assess the quality of life by using the RAND Medical Outcomes Short Form 36 (SF- 36) questionnaire. The population studied had a mean age of 54.60 years with 92.2% were male and 7.8% were female. Most of the respondents were retired (43.3%) followed by service personnel (38.9%). Regarding educational qualification, most of them were between class VIII to SSC and 95.6% were Muslim. The mean monthly income of the respondents was Tk. 18127.78. The findings showed that post CABG respondents possessed a good level of QOL with an average score of 86.0921. The mental components score (87.8571) was found to be higher than physical component score (84.9153). It was found that the association between age and physical functioning domain of physical component was statistically significant (r= -.189*, p